Human Resource Management and Technology: A study of the Status in Nepalese Enterprises (Swarnadwar, 2024)
This article is concentrated on the study of use of technology in HR management system in Nepalese organizations. At present most of the most of the corporate organizations of Nepal use different forms of related software for managing human resource in an effective way to bring effectiveness in performance outcomes. They use technology in various HR activities consisting of recruitment, selection, training, development, financial transactions, performance appraisal, job analysis, HR planning, learning, performance management, career management, compensation management, and maintaining good labour and industrial relation. The main focus of the use of modern technology along with relevant software for managing HR activities is to bring specific system in organizational activities for improving performance to use resources consisting of money, material, machine and information technology in an effective way which helps to maximize productivity, maintaining quality and minimizing cost of products and services which facilitates to improving competitive strengths of the organization in the market. In practice it is found that most of the Nepalese enterprises especially unorganized sectors are still using manual system for managing HR activities of the organization.